Pengembangan Lingkungan Belajar Menggunakan Siklus Pembelajaran Activities, Class Discussion, Exercise Sebagai Upaya Meningkatkan Kemandirian Belajar Mahasiswa - Bety Miliyawaty; Wahid Umar (EDUKASI, 2023)
The design of this research is classroom action research (CAR), following the Kemmis & Mc model. Taggart. The aim is to improve the learning abilities and independence of students of the Unsub mathematics education study program using the ACE (activities, class discussion, exercise) learning cycle in the Introduction to Algebraic Structure (PSA) course. The research subjects were 5th semester students (odd) who contacted the PSA course. The procedure for collecting data is through observation, independent learning questionnaires, interviews, and learning outcomes. Furthermore, the data were analyzed qualitatively following the flow model, with the stages of reducing data, presenting data, and drawing conclusions and verification. The results showed that the PSA lectures used the ACE learning cycle showing that: (1) in the activities phase; students in groups carry out activities outside the classroom; discuss the problems contained in the LKM well, (2) in the class discussion phase, students in groups carry out discussions in the classroom based on problems shared outside the previous class, then present the results, and (3) in the exercise phase ; the lecturer gives practice and test questions to complete. The results of the final tests, observations, and interviews showed that student learning independence increased from 62.15% (cycle I) to 86.05% in cycle II. In conclusion, the application of the ACE learning cycle in the Introduction to Algebraic Structures course can improve the ability and independence of student mathematics teacher candidate learning.